2016
DOI: 10.1007/s00167-016-4284-x
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tracking after isolated medial patellofemoral ligament reconstruction: dynamic evaluation using computed tomography

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
0
36
1
2
Order By: Relevance
“…reported another DKCT study assessing the results of isolated MPFL reconstructions, evaluating various methods to reference and compute anatomical landmarks (Fig. ); another publication presented a similar design with the same purpose.…”
Section: Review Resultsmentioning
confidence: 99%
“…reported another DKCT study assessing the results of isolated MPFL reconstructions, evaluating various methods to reference and compute anatomical landmarks (Fig. ); another publication presented a similar design with the same purpose.…”
Section: Review Resultsmentioning
confidence: 99%
“…Up to 38% to 40% of cases were reported having anterior knee pain in those underwent MPFLR [19]. In additional, Gobbi et al [20] suggested patellar shift and tilt correction will not improve signi cantly when performing isolated MPFLR in patients with RPD, while patellar maltracking is regard as a pathoanatomic risk factor for RPD [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…40 In more recent reports, the collagen matrix has been replaced with a hyaluronan-based scaffold with decreased pain and increased function reported at 4 and 5 years of follow-up. 41 Augmentation of scaffold and allografts for cartilage repair with BMC has limited, but promising results. In patients treated with a polylactide-coglycolide copolymer augmented with BMC or PRP, the BMC group had improved cartilage maturation with greater fill and MRI T2 values closer to that of normal cartilage at 12 months compared with scaffold alone or scaffold with PRP.…”
Section: Clinical Use Of Bmcmentioning
confidence: 99%